Anterior nasal packing: does it affect middle ear pressure? - Pragadeeswaran, K.; Yadavkrishnan, Raj Prakash; Raja, Roopak Visakan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Eustachian tube maintains middle ear pressure equal to that of atmosphere. Its function may be deranged due to variety of factors like adenoids, cleft palate, nasogastric tubes, allergy, nasopharyngeal intubations and also by nasal packing following septal surgery. Our aim was to evaluate the effect of anterior nasal packing protocol, on eustachian tube function, followed in our ENT Department for nasal surgeries. Methods: A descriptive study was done on 60 patients undergoing nasal surgery from March to November 2018 was done in the ENT Department of a tertiary care hospital. All patients underwent pre-operative otoscopic examination followed by tympanometry. Tympanometry was repeated following nasal surgery with nasal pack in situ and again 24 hours after removal of pack. The results of all these 3 impedance audiometries were tabulated and analysed. Results: Pre-operatively both ears in all the patients showed type a tympanometry, which implied normal eustachian tube function. Out of 60 patients who underwent nasal surgeries, 40 had abnormal impedance tympanograms immediately after surgery. 26 patients had abnormal impedance tympanogram after pack removal. These patients were treated with nasal decongestants and antibiotics which were routinely prescribed as a post-operative prophylaxis. These patients 1 week after pack removal recorded a normal tympanogram. Conclusions: Changes in middle ear pressure following nasal packing associated with most nasal surgeries were transient but not severe. Hence, we conclude that anterior nasal packing for 24 hours is considered safe, if no other co-morbid factors for altering middle ear pressures are present.